(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In the scientifc article special atention is paid to the Pedagogical features of environmental and legal education in the family. Some features of the environmental and legal education of pupils are also indicated, and recommendations and suggestions are put forward aimed at improving in this area.